Mendakwah warga tua di Malaysia dan Indonesia - Wan Ibrahim Wan Ahmad,; Zainab Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2006)
The elderly population is growing in all societies including in Malaysia and in Indonesia. This article suggests that the elderly be the main target of Islamic mission. Besides in community as well as in the public places, hospitals can also be one of the strategic places to deliver dakwah. Based on personal experience, this article concludes that non many Muslim preachers deliver their Islamic mission in hospitals in Malaysia. The Muslim preacher should not be hesitant to grab this oppurtinity to deliver Islamic mission to the elderly patients. If the Muslim preacher does not grab this oopurtunity to call people to Islam, as a consequence, it is possible that this vacuum may be taken by Christian missionaries in their christinianization efforts